1978
DOI: 10.1177/030098587801500112
|View full text |Cite
|
Sign up to set email alerts
|

An Electron Microscopic Study of Experimentally-induced HEV Encephalitis

Abstract: Abstract. A gnobiotic piglet, was inoculated intracerebrally with hemagglutinating encephalomyelitis virus (strain VWS72). Mononuclear cells formed vascular cuffs and were disseminated in the brain parenchyma. A few neurons were surrounded by the same kind of cells. Virus particles morphologically similar to coronavirus particles were found in the cytoplasm of both chromatolytic light neurons and hyperchromic dark neurons. The particles were in vesicles of distended endoplasmic reticulum and in the hypertrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…In the present study, PRV infected nerve cells and nonneuronal cells, but HEV antigen was found only in nerve cells. These in vitro findings were consistent with previous in vivo studies in which PRV antigens were found in astrocytes and nerve cells [3,9], whereas HEV particles could be found in nerve cells but were not detected in glial cells and infiltrating cells [11,12,23]. Based on these in vivo and in vitro findings, infectivity of HEV may be more strictly restricted to nerve cells than PRV and rabies virus, for which non-neuronal cells may support viral entry and replication [19].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, PRV infected nerve cells and nonneuronal cells, but HEV antigen was found only in nerve cells. These in vitro findings were consistent with previous in vivo studies in which PRV antigens were found in astrocytes and nerve cells [3,9], whereas HEV particles could be found in nerve cells but were not detected in glial cells and infiltrating cells [11,12,23]. Based on these in vivo and in vitro findings, infectivity of HEV may be more strictly restricted to nerve cells than PRV and rabies virus, for which non-neuronal cells may support viral entry and replication [19].…”
Section: Discussionsupporting
confidence: 90%
“…HEV antigens localized to the periphery of nerve cells in the early stage of infection and then spread to the entire cytoplasm and axon terminals. In general, coronaviruses bind to specific cell surface receptors via the surface projectional glycoproteins and then replicative cycles occur in the cytoplasm [21][22][23][24]. Complete virions assemble to the rough endoplasmic reticulum or Golgi apparatus [15,24,29].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies demonstrated that HEV first oronasally infects the epithelial cells lining the respiratory tract and small intestine and thereafter is delivered retrogradely via peripheral nerves to the central neurons in charge of peristaltic function of the digestive tract, resulting in the so-called vomiting diseases (Andries and Pensaert, 1980). Early electron microscopic (EM) and virological analysis showed that glial cells were not infected by HEV in primarily cultivated astrocytes (Yagami et al, 1993) or in the brains of infected piglets or mice (Meyvisch and Hoorens, 1978;Yagami et al, 1986), indicating that Grant sponsor: RIKEN Brain Science Institute; Grant number: G29 (to T.Has. ); Grant sponsor: MEXT Japan; Grant number: 15650066 (to K.T., T.Has.).…”
Section: Indexing Terms: Coronavirus; Virus Replication; Transsynaptimentioning
confidence: 99%
“…The virus can also spread peripherally from the intestinal myenteric plexuses to the local sensory ganglia of the spinal cord. Electron microscopy yielded the discovery of viral particles within nerve cells, moving from the periphery through the cell cytoplasm to reach the axon (85). However, viral particles could not be found in surrounding glial or in inflammatory cells (85).…”
Section: Pathogenesis and Gross And Histological Lesionsmentioning
confidence: 99%